2016
DOI: 10.1038/ncomms10782
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic leptin action is mediated by histone deacetylase 5

Abstract: Hypothalamic leptin signalling has a key role in food intake and energy-balance control and is often impaired in obese individuals. Here we identify histone deacetylase 5 (HDAC5) as a regulator of leptin signalling and organismal energy balance. Global HDAC5 KO mice have increased food intake and greater diet-induced obesity when fed high-fat diet. Pharmacological and genetic inhibition of HDAC5 activity in the mediobasal hypothalamus increases food intake and modulates pathways implicated in leptin signalling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 63 publications
3
59
0
Order By: Relevance
“…Appropriate expression of Hdac5 has been shown to be required for energy metabolism in mice [25]. The expression of Hdac5 is indeed decreased in the hypothalami of obese mice [25].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Appropriate expression of Hdac5 has been shown to be required for energy metabolism in mice [25]. The expression of Hdac5 is indeed decreased in the hypothalami of obese mice [25].…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, there is emerging evidence implicating Hdac activity in the control of energy metabolism, thus opening an avenue for future targets in metabolic diseases [23]. In the hypothalamus of obese mice fed a HFD, the expression of Hdacs, including Hdac5 , is modified when compared to that of mice fed a chow diet [24], [25]. Hdac5 is required for hypothalamic leptin signaling and food intake, as Hdac5 knockout mice display defective hypothalamic leptin signaling and are more prone to diet-induced obesity compared to wild-type mice [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that HDAC5 was down-regulated in livers from obese mice, at least in part, due to over-nutrition. Interestingly, a recent study found that hypothalamic HDAC5 expression was also reduced in high-fat diet-induced obese mice when compared with chow-fed lean controls [18]. Besides, prolonged fasting induced a decrease in HDAC5 gene expression and an increase after acute refeeding with high-fat diet [18], suggesting that dietary lipids might be important for the regulation of HDAC5 in the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study found that hypothalamic HDAC5 expression was also reduced in high-fat diet-induced obese mice when compared with chow-fed lean controls [18]. Besides, prolonged fasting induced a decrease in HDAC5 gene expression and an increase after acute refeeding with high-fat diet [18], suggesting that dietary lipids might be important for the regulation of HDAC5 in the hypothalamus. Therefore, these two studies may be conceptually relevant, although the precise mechanisms for the down-regulation of HDAC5 remain to be determined.…”
Section: Discussionmentioning
confidence: 99%